Puasa Ramadhan Mengasah Empati dan Solidaritas Sosial - Hanifah Dzakirah; Nurul Fadilah; Hayatul Falah; Lisa Lisa; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Fasting, as one of the main acts of worship in Islam, has a deeper meaning other than just enduring hunger and thirst. It is hoped that this practice can shape individual character, increase spiritual awareness, and have a positive impact on physical and mental health. However, although the spiritual benefits of fasting have been widely discussed, scientific research regarding the impact of fasting on health is still limited. Therefore, this study aims to explore the impact of fasting on physical and psychological health and its influence on self-development. This research uses quantitative methods with an experimental design. A total of 100 participants consisting of individuals who fasted and non-fasted during Ramadan were randomly selected. Data was collected through questionnaires regarding physical and psychological health as well as direct observation of lifestyle before and after fasting. Body mass index (BMI), blood pressure, and stress levels were also measured at two time points: before and after the 30-day fasting period. Data analysis was carried out using the t test to see significant differences between the fasting and non-fasting groups. The results of the study showed that fasting had a significant effect on weight loss, reduced cholesterol levels, and a more stable increase in blood pressure. Psychologically, participants who fasted experienced reduced levels of anxiety and increased concentration and peace of mind. However, this effect is temporary and is more visible in individuals who had a healthy lifestyle before fasting. In addition, most respondents reported increased spiritual closeness and increased feelings of empathy towards others after fasting.